The effect of cochlear implant surgery on vestibular function in adults: A meta-analysis study - Vaz, Fabiane de Castro; Petrus, Leonardo; Martins, Wagner Rodrigues; Silva, Isabella Monteiro de Castro; Lima, Jade Arielly Oliveira; Santos, Nycolle Margarida da Silva; Turri-Silva, Natália; Bahmad, Fayez (Frontiers in Neurology, 2022)
The findings in the literature indicate inconsistency in the complications caused by the implant of electrodes in the cochlea; vestibular alterations and balance disorders are mentioned as the most likely. Purpose: To evaluate, through the results of vestibular function tests, the effects of cochlear implant surgery on postural stability in adults. Hypothesis: From the PICO strategy: Population focuses on adults, Intervention is cochlear implant surgery, Comparisons implanted patients, and Outcomes are the results of cochlear function, the research question was formulated: Are there deficits in vestibular function in adults undergoing cochlear implant placement? Method: Systematic review based on cohort, case-control, and cross-sectional observational studies. Information sources: Databases between 1980-2021: PubMed, Cinahl, Web Of Science, Cochrane, and Scopus. Search strategy using Mesh terms: "Adult", "Cochlear Implant", "Postural Balance", "Posturography", "Cochlear Implant", "Dizziness", "Vertigo", "Vestibular Functional Tests" and "Caloric Tests". Inclusion criteria: Studies with adult patients; Intervention: cochlear implant placement surgery; Comparison: Analysis of vestibular function with vestibular test results and pre-and postoperative symptoms; Outcome: Studies with at least one of the vestibular function tests: computerized vectoelectronystagmography, Vestibular evoked myogenic potentials, Caloric test, Video Head Impulse Test, Head Impulse Test, Videonystagmography and Static and Dynamic Posturography. Exclusion criteria: studies without records of pre-and postoperative data collection and studies with populations under 18 years of age. Screening based on the reading of abstracts and titles was performed independently by 2 reviewers. In the end, with the intermediation of a third reviewer, manuscripts were included. Risk of bias analysis, performed by two other authors, occurred using the JBI. Results: Of the 757 studies, 38 articles met the inclusion criteria. VEMP was the most commonly used test by the studies (44.7%), followed by the caloric test (36.8%), and vHIT (23.6%). Conclusion: Among all vestibular tests investigated, the deleterious effects on vestibular function after cochlear implant surgery were detected with statistical significance using VEMP and Caloric Test. Comparing abnormal and normal results after implant surgery, the vestibular apparatus was evaluated as abnormal results after cochlear implant surgery only in the VEMP test. The other tests analyzed maintained a mostly percentage considered normal results.